Engagement de professeurs et professeures des écoles dans un projet de robotique et de programmation à l’école primaire : des dispositions individuelles aux traductions de prescriptions institutionnelles - Magogeat, Quentin; Chaker, Rawad (Canadian Journal of Education/Revue canadienne de l’éducation, 2026)
We study how teachers engage, invest in, and appropriate a pedagogical innovation project in school robotics, driven by various institutional guidelines in the French context. Drawing on actor-network theory and the distributed cognition paradigm, we aim to understand how and under what conditions teachers engage in an innovative process involving the use of robots, while meeting the requirements of school curricula regarding computer programming in elementary schools, as well as those of pedagogical scenarios resulting from collective production. To answer this question, we cross two sets of data: Verbatim reports from 12 teachers about their reasons for engaging in the PREP project, and video observations of three cases (3 x 4 sessions) of the pedagogical implementation of school robotics lesson plans. The results show different motives for interest in the project (for training, to have new digital resources, among others), which translate into varying levels of engagement within the classroom. The expressed controversies eventually fade away, leading to the stabilization of new practices in favor of educational robotics in five out of the seven schools involved in the project, beyond the experimental period.